A soft energy path for Malaysia - Wong, Kien Keong (1980)
Several studies in industrialized countries have shown strongly that adopting soft energy paths in pursuing continued economic growth can be a reality. This paper first set out the terms of reference for soft energy with the objective of highlighting its feasibility in a country with sunshine all year round. It then proceeded to analyze the energy supply, production, demand, consumption and resource scenario in Malaysia. Present oil production rates seemed unhealthy and a more rational approach to control the extraction rate should be pursued. Logistics curves for the finite resources : oil, natural gas and lignite were generated. The curve for crude oil showed that its production will equal local requirements by 1994 and it will be completely depleted by around 2025. An understanding of these logistics curves allowed for a proper planning of the long term energy strategy for Malaysia.